Insights into Assessing the Genetics of Endometriosis. - Rahmioglu, N; Missmer, SA; Montgomery, G; Zondervan, K (2012)
Endometriosis is a complex disease arising from the interplay between multiple genetic and environmental factors. The genetic variants potentially underlying the hereditary component of endometriosis have been widely investigated through hypothesis-driven candidate gene studies, an approach that generally has proven to be inherently difficult and problematic for a number of reasons. Recently, through major collaborative efforts in the endometriosis research field, hypothesis-free genome-wide approaches have started to provide new insights into potential pathways leading to development of endometriosis, as well as highlighting the phenotypic heterogeneity of the condition. This review summarizes the most recent studies investigating the genetic variation contributing to endometriosis, with a particular focus on genome-wide approaches, and discusses promising future directions of genetic research.